POTRET MANAJEMEN PADA MODEL SATUAN PENDIDIKAN DI SEKOLAH ISLAM TERPADU ITTIHAD MAKASSAR - Julia Mulyana; Zul Fahmi, Ardiansyah, Arismunandar, Ahlun Ansar (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Management is an important aspect in managing an educational unit. Therefore, this research aims to describe how management in the educational unit model at the Makassar Ittihad Integrated Islamic School. The approach used in this research is qualitative by collecting data through interviews, observation and documentation. The subjects of this research were school principals, teachers and staff of SIT Ittihad Makassar. The research results show that in the planning aspect the vision, mission and annual work program are formulated. In the field of curriculum, integration is carried out between general education and religion. Student involvement is encouraged through religious and extracurricular organizations. Human Resources trained through continuous education and training. Public relations is carried out through websites and participation on social media. Strong school culture implement discipline and norms. Finance is obtained from student fees and community donations. As a result, the management model at SIT Ittihad Makassar has been implemented implemented well to achieve the goals of comprehensive Islamic education